The budget impact of brodalumab for the treatment of moderate-to-severe plaque psoriasis on US commercial health plans. (4th May 2018) - Feldman, Steven R.; Wu, Jashin J.; Rastogi, Shipra; Menges, Brandy; Lingohr-Smith, Melissa; Lin, Jay
Abstract: Introduction: Brodalumab is a new biologic approved by the US Food and Drug Administration in 2017 for the treatment of moderate-severe psoriasis. This study evaluated the impact of the introduction of brodalumab on the pharmacy budget on US commercial health plans. Methods: An Excel-based health economic decision analytic model with a US health plan perspective was developed. The model incorporated published moderate-to-severe psoriasis prevalence data; market shares of common biologic drugs, including adalimumab, ustekinumab, secukinumab, ixekizumab, and etanercept, used for the treatment of moderate–severe psoriasis; 2017-year Wholesale Acquisition Costs for the biologic drugs; drug dispensing fee; patient co-pay; and drug contracting discount. Total annual health plan costs for the biologic drugs were estimated. Scenarios with different proportions of patients treated with brodalumab were compared to a control scenario when no brodalumab was used. Results: In a hypothetical commercial health plan covering two million members, 7, 038 moderate-to-severe psoriasis patients were estimated to be eligible for treatment with brodalumab. Prior to brodalumab approval, the proportions of patients treated by other biologics were estimated at 50.8% for adalimumab, 13.5% for ustekinumab, 14.1% for secukinumab, 4.4% for ixekizumab, and 17.2% for etanercept. With a 20% drug price discount applied to all biologics, the annual health plan costs for brodalumab, adalimumab, ustekinumab, secukinumab, ixekizumab, and etanercept were estimated at 37, 224, 49, 166, 55, 084, 56, 061, 64, 396, and 57, 170, respectively. When no brodalumab is used, the total annual pharmacy budget for the biologics used among these patients was estimated at 414, 362, 647. Among scenarios where the proportions of brodalumab usage were 3%, 8%, 16%, and 30%, the total annual pharmacy cost was estimated to be reduced by 3, 698, 129, 9, 861, 677, 19, 723, 355, and 36, 981, 290, respectively. Conclusion: Based on the economic model, brodalumab has the potential to substantially reduce pharmacy expenditures for the treatment of patients with moderate-to-severe plaque psoriasis in the US.